Sustainable Estimation of Cardiovascular Risk with the Predictive Gaziano's Tables without Laboratory - José Betancourt Bethencourt; Gerardo Brunet Bernal; Moura Revueltas Agüero (Revista Finlay)
Background: identifying cardiovascular risk factors is very important, because by taking actions to counteract them, the probability of presenting cardiovascular and cerebrovascular diseases can decrease significantly. Objective: to demonstrate the feasibility of using the Gaziano's tables without a laboratory to estimate cardiovascular risk. Method: 72 health workers linked to the University of Medical Sciences of Camagüey were interviewed during November 2021, in addition, their blood pressure, weight and height were measured and they were asked in the survey: age, if they were diabetic and if they smoked. These people underwent Cronbach's Alpha reliability test. They were asked if they had other modifiable habits (frequency of physical exercise, consumption of alcoholic beverages, if they have snacks between meals and if they add salt to them). Cardiovascular risk was determined with the Gaziano's tables without laboratory. Results: 21 % of the interviewees presented high and very high risk. Of the study participants, 40 % declared they were hypertensive. The mean body mass index was 29.3±4 kg/m2 and there was a correlation between this and age, with high and very high risks. Conclusions: Gaziano's predictive tables without laboratory were feasible to apply, their use could be extended to the first level of health care, as it is a sustainable, non-invasive and fast method in times of the COVID-19 pandemic. Knowledge of its use in undergraduate and postgraduate teaching should be transmitted.